The Predicament of Indian Women as Depicted in Sarojini Sahoo‟s Novel the Dark Abode - B.S., Farzana; M. , Rakesh Babu (International Journal of Psychosocial Rehabilitation, 2020)
India is traditionally a patriarchal and patrilineal society where individual rights are subject to social role expectations. In such societal framework feminine mystique is glorified and a woman’s individual self has no recognition. Self-effacement remains as her normal way of life. Woman is supposed to be an ideal wife and an ideal mother and a home- maker. She is expected to be an epitome of virtue. Her supreme duty is to keep the husband happy and satisfied. She should also completely devote herself to the happiness of the household. It is generally seen women sustains life, she is the preserver of the home and a protector of culture. Even though woman is regarded as ‘Shakti’ and ‘Lakshmi’ the society expects her to have a subdued and submissive existence. This paper discusses the burden of such expectations becomes a form of oppression for women.